El Cuatro Paso en el Desarrollo Sostenible de la Comunidad: Identificar Indicadores para Medir el Progreso - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS)
This document is FCS7217-Span, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.